Aspects of violence leading to distress and changed attitudes for physiotherapists: A qualitative investigation. (December 2022) - Van Fossen, Jenna A.; Chang, Chu-Hsiang
Abstract: Objective: Physiotherapists are often the targets of workplace violence. We investigated how physiotherapists make sense of their exposure experiences, and what aspects of their experiences of workplace violence lead to negative reactions and changed attitudes towards the work organization. Design: Qualitative interview study. Methods: We conducted individual semi-structured interviews with 82 physiotherapists across a range of care settings. Interviews were recorded and transcribed. We then conducted an inductive content analysis of the transcribed interviews. Results: We found two themes representing meaningful characteristics of exposure incidents for determining reactions: attributions of intent to cause personal harm and acceptance of violence. We found three themes under changed attitudes: awareness of risk, adequacy of the organization's actions to prevent violence, and satisfaction with organizational support. Physiotherapists were more likely to experience psychological distress when they perceived that perpetrators intended to cause harm and were cognitively coherent. Following violence, physiotherapists were also more cognizant of risk in their profession. Changes in attitudes about the organization were driven by satisfaction with violence prevention measures and organizational support. Conclusions: Organizations should develop policies to prevent violence and provide victims with additional support, particularly when victims express that they believe that violence was committed intentionally and when the perpetrators are not cognitively impaired. Physiotherapists may be able to minimize the effects of violence exposure by reflecting on their exposure experiences and attributing the exposure to external factors.